Разработка чайного сервиза; Gaudeamus Igitur; № 1 - Цыглова А. В. Александра Викторовна; Радченко В. Ю. Валерия Юрьевна; Давыдова Е. М. Евгения Михайловна; Ризен Ю. С. Юлия Сергеевна (2015, 2015)
Заглавие с экрана